2017
DOI: 10.1007/s10096-017-3032-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility profiles among Campylobacter isolates obtained from international travelers between 2007 and 2014

Abstract: Campylobacter infection is a common cause of diarrhea among international travelers. We studied antibiotic resistance patterns among Campylobacter isolates obtained from international travelers according to travel destination. Three collections of isolates obtained from international travelers between 2007 and 2014 (Institute of Tropical Medicine, the “Laboratoire Hospitalier Universitaire de Bruxelles “and the Belgian National Reference Centre for Campylobacter) were used. Isolates were tested for minimal inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 13 publications
4
29
0
Order By: Relevance
“…However, in many countries, Campylobacter isolates are increasingly resistant to fluoroquinolones (ciprofloxacin and nalidixic acid) (EFSA & ECDC, ; Riley, Eshaghi, Olsha, Allen, & Patel, ; Tang, Skovgard, Pedersen et al., ). In a study of antibiotic susceptibility among Campylobacter isolates obtained from international travellers between 2007 and 2014, ciprofloxacin resistance tended to increase over time from 54% to 72% (Post et al., ). Furthermore, increased resistance is also reported for isolates from animals in countries where quinolones or fluoroquinolones administered via feed or water neither are neither authorized nor used (Swedres‐Svarm, ).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in many countries, Campylobacter isolates are increasingly resistant to fluoroquinolones (ciprofloxacin and nalidixic acid) (EFSA & ECDC, ; Riley, Eshaghi, Olsha, Allen, & Patel, ; Tang, Skovgard, Pedersen et al., ). In a study of antibiotic susceptibility among Campylobacter isolates obtained from international travellers between 2007 and 2014, ciprofloxacin resistance tended to increase over time from 54% to 72% (Post et al., ). Furthermore, increased resistance is also reported for isolates from animals in countries where quinolones or fluoroquinolones administered via feed or water neither are neither authorized nor used (Swedres‐Svarm, ).…”
Section: Treatmentmentioning
confidence: 99%
“…Almost all humans infected by Campylobacter recover without specific treatment; however, antimicrobial therapy is warranted for patients with bacteremia or a life-threatening condition. Erythromycin is considered the optimal drug for treatment of campylobacteriosis, as it is easy to administer and has a narrow spectrum of activity (Acheson & Allos, 2001 | 41 between 2007 and 2014, ciprofloxacin resistance tended to increase over time from 54% to 72% (Post et al, 2017). Furthermore, increased resistance is also reported for isolates from animals in countries where quinolones or fluoroquinolones administered via feed or water neither are neither authorized nor used (Swedres-Svarm, 2015).…”
Section: Tr Eatmen Tmentioning
confidence: 99%
“…Even at a low infectious dose of only a few hundred bacteria there is a reasonable chance that an infection will be established in humans [ 3 , 4 ]. Campylobacter has developed resistance to several antimicrobials, in particular, resistance to fluoroquinolones [ 5 ]. A recent study conducted in Luxembourg found that around 61% of Campylobacter infections in humans were attributed to poultry meat, 33%, 5% and 0.6% were attributed to ruminant meat, the environment and pork meat, respectively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two PBGs, cam P and mec A ( Campylobacter and Staphylococcus , respectively), were also detected to be co‐present with all ARGs except tet A. This result is supported by the continuous identification of Staphylococcus and Campylobacter resistant to various antibiotics, such as β‐lactam, ciprofloxacin, and erythromycin (Narvaez‐Bravo, Taboada, Mutschall, & Aslam, ; Post et al., ; Qekwana, Oguttu, Sithole, & Odoi, ).…”
Section: Resultsmentioning
confidence: 76%